Green or nongreen innovation? Different strategic preferences among subsidized enterprises with different ownership types. (1st February 2020) - Liu, Zimeng; Li, Xu; Peng, Xuerong; Lee, Seoki
Abstract: Governments often turn to subsidies to boost enterprises' innovation activities, which gives subsidized enterprises room for allocating the subsidies among different innovation activities. Taking insights from institutional logic theory, this paper proposes that enterprises exhibit different subsidy-allocation behaviors between nongreen and green innovations and that the positive effect of subsidies on nongreen innovation is greater than that on green innovation due to the double-spillover problem that is pertinent to green innovation. Further, this paper argues that innovation intensity varies from privately-owned enterprises to local and central state-owned enterprises and that the underlying reason for this phenomenon is that enterprises with different ownership structures behave with different institutional logics, face different environmental and innovation pressures, and hold different innovative resource and capability endowments. We test these hypotheses by using longitudinal data (2010–2015) on 175 publicly-traded firms in the pharmaceutical industry in China. Overall, the results support most of the hypotheses. Highlights: The effects of governmental subsidies on green and nongreen innovations were examined. The moderating role of ownership types between innovation subsidies and green/nongreen innovation was examined. Five-year panel data from 175 publicly traded Chinese pharmaceutical firms were used to test the hypotheses.